Impact of GBL on student performance and learning behaviour: experience in UiTM Melaka / Rani Diana Othman, Ismadi Md Badarudin and Nurul Hidayah Ahamad Nawawi - Othman, Rani Diana; Md Badarudin, Ismail; Ahamad Nawawi, Nurul Hidayah (UiTM Press, 2020)
Computer integrated system has commonly used to increase classroom engagement by educators in schools and universities. It is to enhance students' learning interest toward studies and improve their academic result which relates to weakness of the traditional based learning process. Moving towards the 21th century, education environment has also introduced with Game-Based Learning (GBL) used to encourage students to participate in learning, while having fun and creating more interesting learning process. As an interactive learning setting, GBL provides an opportunity for the teaching process to evolve through the incorporation of game elements. GBL is suggested able to capture students' attention, motivation towards goals, promote competition, effective teamwork and improve communication. This study investigates the effectiveness of a game based learning program adapted from a television show known as 'Who Wants To Be A Millionaire?' to assess students' academic performance. It compares students' performance before and after the game was introduced in the learning process.